In Situ Genetic Evaluation of European Larch Across Climatic Regions Using Marker-Based Pedigree Reconstruction - Lstibůrek, Milan; Schueler, Silvio; El-Kassaby, Yousry A.; Hodge, Gary R.; Stejskal, Jan; Korecký, Jičí; Škorpík, Petr; Konrad, Heino; Geburek, Thomas (Frontiers in Genetics, 2020)
Sustainable and efficient forestry in a rapidly changing climate is a daunting task. The sessile nature of trees makes adaptation to climate change challenging; thereby ecological services and economic potential are under risk. Current long-term and costly gene resources management practices have been primarily directed at few economically important species, and are confined to defined ecological boundaries. Here we present a novel in situ gene-resource management approach that conserves forest biodiversity and improves productivity and adaptation through utilizing basic forest regeneration installations located across a wide range of environments without the reliance on structured tree breeding/conservation methods. We utilized 4,267 25- to 35-year-old European larch trees growing on 21 reforestation installations across four distinct climatic regions in Austria. With the aid of marker-based pedigree reconstruction, we applied multi-trait, multi-site quantitative genetic analyses that enabled the identification of broadly adapted and productive individuals. Height and wood density, proxies to fitness and productivity, yielded in situ heritability estimates of 0.23±0.065 and 0.30±0.073, values similar to those from traditional “structured” pedigrees methods. In addition, individual trees selected with this approach are expected to yield genetic response of 1.1 and 0.7 standard deviations for fitness and productivity attributes, respectively, and be broadly adapted to a range of climatic conditions. Genetic evaluation across broad climatic gradients permitted delineation of suitable reforestation areas under current and future climates. This simple and resource-efficient management of gene resources is applicable to most tree species.